Assessment of eating attitudes and body satisfaction among high school adolescents in Turkey - Bulduk, Emre Özgür; Bulduk, Sıdıka; Özkula, Güler (Progress in Nutrition, 2018)
Background/aims:  This research aimed to investigate the relationship between eating attitudes and body satisfaction among adolescents attending high school in Ankara, the capital city of Turkey. Methods: The participants were 718 males and 761 females, in total 1479 adolescents aged between 13 and 18 years. The Eating Attitude Test-26 (EAT-26) and Body Cathexis Scale (BCS) were used to assess eating attitudes and body satisfaction respectively. Data from the study were evaluated statistically by chi-square test. Results: Our results showed that 2.93 % of males and 40.07 of females faced a high risk of having an eating disorder. Our findings confirm that females are more at risk of eating disorders. The BCS of males (90.8 ± 20.8) was found significantly higher than females (81.3 ± 16.8) ( p